The politics of strategy: why government agencies conduct major strategic reviews. (5th May 2015) - Tama, Jordan
Abstract: In recent years, United States (US) policymakers have instituted quadrennial strategy reviews in several major policy areas. In this article, I examine why policymakers have initiated these large strategic reviews, and why a particular model for them has diffused from the US Defense Department to other government agencies. I find that policymakers have initiated the reviews principally to spur organisational change in agencies and influence the relationship between agencies and the Congress, and that policymakers have replicated the Defense Department's review model because of that department's strong political support. My findings suggest more generally that formal strategy activities are often driven more by legislative-executive and bureaucratic politics than by a search for new strategic ideas. Commonalities between the diffusion of quadrennial reviews in the US and the diffusion of other strategy and planning processes internationally underscore the broader applicability and significance of these findings.